Strengthening of steel and concrete composite trusses by unbonded external prestressing - Chanvaivit, Kanokpat (ASEAN engineering journal)
In this paper, the method of strengthening steel and concrete composite trusses by using unbonded external prestresssing was presented. Based on the experimental results compared with the analytical calculations, the structures are believed to perform better than the conventional composite trusses. The additional unbonded mono-strand external prestressing tendon of 7.9% of the tension bottom chord cross sectional area results in the 20% higher load carrying capacity. Moreover, there is the advantage of the additional prestressing to improve the accuracy of the flexural stiffness determination by using the transformed section method for the truss-like structural system. However, to maintain the ductile failure mode, the amount of strengthening tendon should be limited for the required rotational capacity. In conclusion, this method can be useful in the upgrading of the existing composite trusses for both the flexural strength and serviceability.